Analisis Kepuasan Pemakai Terhadap Pelayanan Perpustakaan Nasional Provinsi Daerah Istimewa Yogyakarta = An Analysis on User Satisfaction of the Services Provided by National Library of Yogyakarta Province - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT Library as information source and service is expected to be able to disseminate information to the users in a satisfactory way. The study that measures "User Satisfaction on The Services Provided by National Library of Yogyakarta Province" aims at indentifying satisfaction level of the library and the influencing factors. This study is a descriptive research, The population of study was 11027 members of National Library of Yogyakarta Province in 2000, while 200 of who were taken as the sample using proportionate stratified random sampling. Data were collected by distributing questionnaires that have been tested for the validity and reliability by Pearson's product moment and alpha coefficient. The data were analyzed by descriptive statistics by presenting the table that contains frequency of responses on the variables of studied and regression analysis. The analysis was based on the rating on the service provided bay National Library of Yogyakarta Province that include: 1) tangibles